2022
DOI: 10.1037/sgd0000445
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Acceptance of Sexuality Inventory (SASI): Development and validation.

Abstract: King's College LondonDue to exposure to societal stigma, self-acceptance of sexuality can be a challenging process for individuals who identify as lesbian, gay, bisexual, queer, or with other minority sexual identities (LGBQϩ). Quantitative research in this area is limited, and there is a lack of appropriately validated self-report questionnaires to assess self-acceptance of sexuality. Therefore, the aim of the current study was to develop a measure of self-acceptance of sexuality. Items for the new Self-Accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Participants highlighted a number of identity-related dilemmas, such as identity confusion and acceptance, which had an impact on wellbeing and were considered as important for targeting in DBT, congruent with identity development and minority stress research (Camp et al ., 2020; Camp et al ., 2022; Cass, 1979; Hendricks and Testa, 2012; Meyer, 2003). It may also be particularly important to focus on identity in DBT for adolescents given the importance of this developmental stage for identity evolution and acceptance (Hall et al ., 2021; Katz-Wise et al ., 2017; Meyer, 2003; Savin-Williams and Ream, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants highlighted a number of identity-related dilemmas, such as identity confusion and acceptance, which had an impact on wellbeing and were considered as important for targeting in DBT, congruent with identity development and minority stress research (Camp et al ., 2020; Camp et al ., 2022; Cass, 1979; Hendricks and Testa, 2012; Meyer, 2003). It may also be particularly important to focus on identity in DBT for adolescents given the importance of this developmental stage for identity evolution and acceptance (Hall et al ., 2021; Katz-Wise et al ., 2017; Meyer, 2003; Savin-Williams and Ream, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Influential models for the first author included the minority stress (Meyer, 2003; Hendricks and Testa, 2012), psychological mediation frameworks (Hatzenbuehler, 2009), models detailing a social justice lens on scientific endeavours in this area (e.g. Pachankis, 2018), and self-acceptance models (Camp et al ., 2020; Camp et al ., 2022). The first author also has particular interests in frameworks adapting DBT and similar models to minoritised groups (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…We further found that LDS SGMs reported coming out experiences were beneficial when they focused on self-understanding and self-acceptance. Self-understanding and acceptance are helpful for SGMs more generally in navigating their sexual and/or gender identities (Camp et al 2020b). It may be that increasing self-understanding and self-acceptance allows SGMs to approach coming out conversations with greater knowledge of who they are and how to vocalize that to others.…”
Section: Sgm Approaches Relating To Positive Coming Out Experiencesmentioning
confidence: 99%
“…Given that the description and explanation of how the dimensions that conform sexuality work involves an analysis through groups and collectives defined, among other criteria, by gender and sexual orientation, measurement invariance testing acquires an unquestionable importance in the field of human sexuality. In this sense, the production in recent years reflects the interest in examining the factorial invariance of scales that assess different dimensions of sexuality [12,18,25,42,[59][60][61][62][63][64][65][66][67]. The purpose of this study was to examine the measurement invariance across sexual orientation of the Spanish versions of three scales that assess sexual attitudes: the Sexual Opinion Survey (SOS) [23] by Vallejo-Medina et al [28], the Hurlbert Index of Sexual Fantasy [43] by Desvarieux et al [44], and the Negative Attitudes Toward Masturbation Inventory (NATMI) [51] by Cervilla et al [42].…”
Section: Introductionmentioning
confidence: 99%